Screening for WSSV in crustacean from marine areas of Buenos Aires, Argentina - Martorelli, Sergio Roberto (2017)
In total 374 specimens corresponding to four species of shrimp: Artemesia longinaris, Pleoticus muelleri, Peisospetrunkevitchii, Palaemon macrodactylus, and two species of crabs: Neohelice granulata and Cyrtograpsus angulatus were studiedin the search of white spot syndrome virus (WSSV). The crustaceans were collected in the estuary of Bahia Blanca, the port of Mardel Plata and the Samborombón Bay, Argentina, between 2010 and 2014. A polymerase chain reaction (PCR) analysis in all of themhas not detected any virus presence. These new results suggest that the discovery of infected shrimp in 2008-09 in the BahiaBlanca estuary may have been a one-time local event, promoted by special conditions of seawater temperature inside the estuary,coincident with the presence of a virus carrier or transporter. To determine if the virus was finally installed in the estuary of BahiaBlanca more screening are needed coming from a larger number of shrimp samples. These studies will be necessary mainly in A.longinaris (Penaeidae) since this family of shrimps is most susceptible to be affected by WSSV.